Factors That Determine the Successful Management of Ectopic Pregnancy Through Methotrexate Injections - Baiq Ayu Rahmawati; Amelia Wahyu Maharani; Ali Ramzi; Muhammad Rizkinov Jumsa (Jurnal Biologi Tropis, 2023)
Ectopic pregnancy is a pregnancy that occurs when the gestational sac is located outside the uterus. Methotrexate administered intramuscularly (IM) is the standard management in the therapy of ectopic pregnancies. The success of managing ectopic pregnancies using methotrexate is influenced by various factors. This literature review aims to provide related information because a sufficient understanding of the factors that affect the success of methotrexate use in ectopic pregnancies is crucial to prevent complications, reduce morbidity and mortality rates resulting from ectopic pregnancies. In this literature review we conducted a search on the National Center for Biotechnology Information (NCBI) and Google Scholar database using the search keyword factors, methotrexate, and ectopic pregnancy. The success of treating ectopic pregnancies using methotrexate is influenced by various factors, such as the initial β-hCG levels, the size of the ectopic mass, peritoneal fluid, maternal age, gestational age, previous spontaneous miscarriage, gravida, parity, abortion, and the percentage of a history of previous ectopic pregnancies. However, most studies have found that the primary factor influencing success is the initial β-hCG levels.